Wordsworth's revisitings - Gill, Stephen (Oxford : Oxford University Press, 2011)
Nothing was more important to Wordsworth than tracing the evidence that affinities had been preserved between all the stages of the life of man. Stephen Gill explores the ways in which the poet attempted as an artist to maintain such continuities and shows how revisitings of various kinds are at the heart of his creativity.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Wordsworth, William, -- 1770-1850 -- Criticism and interpretation